The Rise in Corporate Saving and Cash Holding in Advanced Economies : Aggregate and Firm Level Trends - Dao, Mai Chi.; Maggi, Chiara (Washington, D.C. : International Monetary Fund, 2018)
Using cross-country national accounts and firm-level data, we document a broad-based trend in rising gross saving and net lending of non-financial corporates across major industrialized countries over the last two decades, though most pronounced in countries with persistent current account surpluses. We find that this trend holds consistently across major industries, and is concentrated among large firms, driven by rising profitability, lower financing costs, and reduced tax rates. At the same time, higher gross corporate saving have not supported a commensurate increase in fixed capital investment, but instead led to a build-up of liquid financial assets (cash). The determinants of corporate cash holding and saving are also broad-based across countries, with the growth in assets of large firms, R and D intensity, and lower effective tax rates accounting for most of the increase over the last 15 years.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet